In the countryside: development with extractivism - Hidalgo Flor, Francisco (2018)
Unlike most of Latin America, Ecuador has experienced in the 21st century, between 2006 and 2016, its most intense developmental phase in the history of the country. This has happened under a regime that calls itself progressive, which has announced the recovery of the state as the means to regain an apparent stability in the political system. The most palpable example of such stability is the continuity of the same ruler for a decade, having during the last six years an absolute majority in the legislature. Simultaneously and in parallel, the deployment of the countryside in Ecuador is strongly traversed by two coordinates that previously appeared in theory as opposed but in practice have been conjugated: developmentalism and extractivism. The execution of this program has been sustained by the huge investment and credit coming from China, with considerable incursions into the strategic sectors of the Ecuadorian state.